Multiscale polycentric governance in transformative adaptation to climate change: a tool guide - Amarasinghe, Upali A.; Amarnath, Giriraj; Ukwattage, Sachini; Wickremasinghe, H. (International Water Management Institute, 2023)
This innovation brief presents a set of standard operating procedures (SOPs) to operationalize multiscale polycentric governance (MPG) in using transformative adaptation options (TAOs) to enhance systemic resilience against climate change. The SOPs deal with identifying the transformative characteristics of adaptation options, the institutions involved in an MPG system, and the framework for assessing the ex-ante governance influence of TAOs in enhancing climate resilience via various intermediate impact dimensions. Such an evaluation can help in the allocation of investments in potential governance components to ensure enhanced intermediate outputs, leading to sustainable outcomes of climate resilience and rural welfare.